Treatment of bone pain secondary to metastases using samarium-153-EDTMP - Etchebehere, Elba Cristina Sá de Camargo (2004)
CONTEXT: More than 50% of patients with prostate, breast or lung cancer will develop painful bone metastases. The purpose of treating bone metastases is to relieve pain, reduce the use of steroids and to maintain motion. OBJECTIVE: To evaluate the use of samarium-153- EDTMP (153Sm-EDTMP) for the treatment of bone pain secondary to metastases that is refractory to clinical management. TYPE OF STUDY: Retrospective. SETTING: Division of Nuclear Medicine, Universidade Estadual de Campinas (Unicamp). METHODS: Fifty-eight patients were studied (34 males) with mean age 62 years; 31 patients had prostate cancer, 20 had breast cancer, three had lung cancer, one had lung hemangioendothelioma, one had parathyroid adenocarcinoma, one had osteosarcoma and one had an unknown primary tumor. All patients had multiple bone metastases demonstrated by bone scintigraphy using 99mTcMDP,and were treated with 153Sm-EDTMP. Response to treatment was graded as good (pain reduction of 50-100%), intermediate (25-49%) and poor (0-24%). RESULTS: All patients showed good uptake of 153Sm-EDTMP by bone metastases. Among the patients with prostate cancer, intermediate or good response to therapy occurred in 80.6% (25 patients) and poor response in 19.4% (6). Among the patients with breast cancer, 85% (17) showed intermediate or good response to therapy while 15% (3) showed poor response. All three patients with lung cancer showed poor response to treatment. The lung hemangioendothelioma and unknown primary lesion patients showed intermediate response to treatment; the osteosarcoma and parathyroid adenocarcinoma patients showed good response to treatment. No significant myelotoxicity occurred. DISCUSSION: Pain control is important for improving the quality of life of patients with advanced cancers. The mechanism by which pain is relieved with the use of radionuclides is still not yet completely understood, however, the treatment is simple and provides a low risk of mielotoxicity. CONCLUSION: Treatment with 153Sm-EDTMP can control the pain secondary to bone metastases effectively in most patients with breast and prostate cancer without significant side effects.